ANALISIS DAMPAK PANDEMI COVID-19 TERHADAP PENGGUNAAN TRANSAKSI DIGITAL (PEMBAYARAN SECARA CASHLESS) PADA UMKM KOTA BAUBAU - Laode Muhammad Hasrul Adan (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
This study aims to determine the impact of the Covid-19 pandemic on the use of digital transactions (cashless payments) in SMEs in Baubau city. The research method used in this research is qualitative analysis with a descriptive approach. The objects of research are MSMEs registered with the Baubau city cooperative office, namely Lawa Bistro, Rezky Distro, and Nadel Cosmetic. Data collection methods through observation, interviews, and documentation with data analysis techniques collect, compile and analyze data for problem solving in research so that a conclusion can be drawn. The results showed that the use of digital transactions (cashless payments) during the Covid-19 pandemic, greatly facilitated and helped MSME players, although the use of the types of digital transactions used was still limited via ATM transfers, Mobile banking and Q-RIS, but greatly enlivened Baubau city MSMEs. In using these digital transactions, MSME players still lack understanding of the functions and risks of the applications used. The impact of digital transactions (cashless payments) during the Covid-19 pandemic MSMEs, it is concluded that the use of digital transactions during the Covid-19 pandemic has a huge impact on MSMEs.